Managerial ability and bank failure. Issue 4 (23rd February 2021) - Luu, Hiep Ngoc; Doan, Thang Ngoc; Anh, Pham Thi Hoang
ABSTRACT: Bank failure is a major concern for the authoritative bodies and market participants because of the possible contagion across the financial sector and the subsequent collapse of the economic system. This paper investigates the impact of managerial ability on bank failure. We find that more ably managed banks experienced lower failure probability. Further analyses provide support to this finding and reveal that more ably managed banks are associated with more adequate capital, better asset quality, greater efficiency in the allocation of resources, higher liquidity and lower risk.